Law Enforcement Against Foreign Nationals with Expired Travel Documents and Residence Permits - Suprihantoro, Ikhwan; Dwidja Priyatno; Trini Handayani; Aji Mulyana (Yayasan Studi Cendekia Indonesia (YSCI), 2024)
Increased global mobility poses complex challenges for Indonesia, particularly in the management of foreign nationals (WNA) whose travel documents have expired. This research analyses the law enforcement process against foreigners whose travel documents and residence permits have expired, with a focus on the case study of the Cianjur District Court Decision Number 303/Pid.Sus/2023/PN Cjr. The research method used is normative juridical, which examines laws and regulations related to immigration and the implementation of immigration criminal investigations. The results showed that the Immigration Office Class III Non TPI Cianjur performs the function of supervision and enforcement of immigration law properly, as stipulated in Law Number 6 Year 2011 on Immigration. The case of a Nigerian foreigner, Oluchukwu Basil Ezebuo, who used an expired travel document and residence permit, became a concrete illustration of how the investigation and prosecution procedures were carried out. Enforcement involves administrative checks, seizures, and prosecution up to court hearings. The judge's verdict imposing a one-year imprisonment and a fine of five million rupiah on the defendant was considered to have fulfilled the principles of justice and legal certainty. This research concludes that strict law enforcement is needed to maintain state sovereignty and prevent the misuse of immigration documents by foreigners.